Identifying frailty in the Emergency Department—feasibility study - Amy Elliott; Kay Phelps; Emma Regen; Simon Conroy (2017)
identifying the most at risk older people in Emergency Departments (EDs) may help guide clinical practice, and service improvement in emergency care, but little is known about how to implement such tools in practice. consensus building was used to determine the desirable characteristics of a risk stratification process, including focus groups and literature reviewing. Candidate tools were tested using clinical vignettes in semi-structured interviews with a range of clinicians working in one large ED, assessing speed of use, ease of use and agreement with clinical judgement. The primary outcome was the likelihood of future use of a given frailty tool. the ideal tool characteristics included brevity (<1 min), simplicity and multidimensionality; tools selected for testing included the Identification of Seniors At Risk, Clinical Frailty Scale, PRISMA-7 and Silver Code. One hundred and twenty-one staff members (43% of the total ED workforce) were recruited from one large ED in the East Midlands. Two hundred and thirty-six individual frailty tool assessments were undertaken using 1 of 10 clinical vignettes; 75% of staff stated that they would use at least one of the tools again, with no significant differences between the individual tools. The median time to complete the tool was around 1 min per patient for all four tools. There were no significant differences in timing, ease of use or agreement with clinical judgement between tools. validated risk stratification tools are quick, simple, easy to use and 75% of staff would use the tools again in the future.